Resident Education in Complex Obstetric Procedures: Are We Adequately Preparing Tomorrow's Obstetricians? - Dotters-Katz, Sarah K.; Gray, Beverly; Heine, Robert Phillips; Propst, Katie (American Journal of Perinatology, 2019)
Objectives The Accreditation Council for Graduate Medical Education (ACGME) milestones for obstetrics and gynecology (OB/GYN) residents include obstetrical technical skills. We sought to describe resident experience with surgical obstetrics and comfort performing procedures independently postgraduation.Study Design An anonymous 27-question e-survey was sent to OB/GYN residents in United States in March 2018, using the Council of Resident Education in Obstetrics and Gynecology coordinator listserv. Complex obstetric procedures included: forceps-assisted vaginal delivery (FAVD) and vacuum-assisted vaginal delivery (VAVD), cerclage, breech second twin, breech delivery, perineal repairs, and cesarean hysterectomy. Technical skill questions included experience as primary surgeon, comfort performing procedures independently, and for 4th year residents—comfort performing procedures postresidency. Demographic information was queried. Descriptive statistics was used to analyze responses.Results A total of 417 residents completed the survey. Respondents were 88% female, 75% from academic programs, and 48% postgraduate year 3 and 4. Among all residents, many had been primary surgeon in operative vaginal deliveries (51% FAVD, 72% VAVD), fewer for breech vaginal delivery (21%), breech second twin (34%), cesarean hysterectomy (21%), and 4th degree repairs (37%). All 4th-year respondents stated that they would feel comfortable performing either VAVD or FAVD postresidency. Note that 17, 33, 28, and 74% would not feel comfortable performing a 4th degree repair, cesarean hysterectomy, breech second twin, and breech vaginal delivery, respectively, postresidency.Conclusion Despite ACGME recommendations, data suggest that many graduating residents may not be comfortable with these complex procedures.
Keywords: breech; forceps; obstetric procedures; resident education